ã€ŠæˆåŠŸä¹‹è·¯ã€‹çš„æ±‰è¯æˆè¯ä¸Žå°å°¼è¯æˆè¯çš„è¯ä¹‰å¯¹æ¯” - Steffani, Dede Indah Sari; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This research aims to further explore the comparison of the meaning of Chinese idiom and methaphorâ€™s body in the book of â€œRoad to Successâ€ with the Indonesian idiom. The research methods that used are research methods of library and comparative research methods. The objects of the research are the 6 volumes of the comprehensive learning materials